Energy budget, economics and yield performance of millet based crop rota tions with Indian mustard in Hisar district of Haryana (India) - AK Dhaka,; Bhagat Singh,; RD Jat,; Kamal,; Dalip Kumar Bishnoi, (Journal of Oilseed Brassica, 2025)
Millets and pulses are the most important dryland crops grown in both Kharif and Rabi seasons in the semi-arid regions of the country for food, feed and animal fodder. These crops also show considerable resilience to changing climate (drought, heat and nutrient stresses). For diversification of  Pearl millet-Chickpea rotation, adoption of small millets (finger millet, foxtail millet, proso millet, little millet, brown top millet, barnyard  millet, and kodo millet) in addition to pearl millet may be viable option.A field experiment was carried out at CCS Haryana  Agricultural University, Hisar, Haryana, India during 2022-23 in randomized block design in Kharif and Rabi season, replicated thrice with eight treatments (foxtail millet, little millet, browntop millet, proso millet, kodo millet, barnyard millet, finger millet and pearl millet) in Kharif season and eight crop rotations (foxtail millet- Indian mustard, little millet- Indian mustard, browntop millet- Indian mustard,  proso millet- Indian mustard , kodo millet- Indian  mustard, barnyard millet - Indian mustard, finger millet Indian  mustard and pearl millet - Indian mustard) in Rabi season to evaluate yield and economic performance eight millet based crop  rotations with Indian mustard. During Kharif  season among all millets (foxtail millet, little millet, browntop millet,  proso millet,  kodo millet,  barnyard millet, finger millet and pearl millet) tested, Pearlmillet was found most suitable, which produced significantly higher grain yield (2462 kg/ha), biological yield (10066 kg/ha), net energy returns (121552 MJ/ha), Energy intensiveness (14.0 MJ/USD), human energy profitability (133.3 MJ/ha) compared to all other millets. In Rabi season Indian mustard  sown after Pearl millet recorded significantly higher seed yield (3492 kg/ha), biological yield (20666 kg/ha), net returns (Rs. 120471/ha)  and B:C (2.97) compared to other crop rotations but Indian mustard sown after foxtail millet recorded higher  net energy returns (250664 MJ/ha), energy ratio (25.50), energy profitability (24.50 MJ/ha) and  human energy profitability (267.8 MJ/ha).